The Relationship of Therapist Verbal Response Mode and Client Good Moments in Short Term Dynamic Psychotherapy - De Stefano, Jack; Bernardelli, Antonio; Stalikas, Anastassios; Iwakabe, Shigeru (Canadian Journal of Counselling and Psychotherapy, 2007)
Using a single case quantitative analysis, the relation between therapist verbal response mode and client good moments was examined to provide information about the process of a short-term dynamic psychotherapy (STDP) developed by Davanloo (1978, 1980). Independent judges rated three sessions (early, middle and late) of a complete sixteen session treatment using the Hill Counselor Verbal Response Category System-Revised (HCVRCS-R) (Friedlander, 1982) and the Category System of Client Good Moments (CSCGM) (Mahrer, 1988). Chi-square analyses revealed a significant association between therapist verbal responses and the subsequent occurrence of client good moments. The results are discussed in terms of their clinical and research implications.